Rosa roxburghii fermented juice mitigates LPS-induced acute lung injury by modulation of intestinal flora and metabolites - Chen, Zhiyu; Zhang, Shuo; Sun, Xiaodong; Meng, Duo; Lai, Chencen; Zhang, Min; Wang, Pengjiao; Huang, Xuncai; Gao, Xiuli (Frontiers in Microbiology, 2024)
Acute lung injury represents a formidable challenge in pulmonary pathology, characterized by high mortality and morbidity rates, compounded by the lack of effective pharmacotherapeutic options. Rosa roxburghii Tratt, an exceptionally unique fruit cultivated in the lush regions of southwestern China, is highly esteemed for its rich nutritional content and diverse functional properties. Fermentation, a superior method of food preservation, has the potential to significantly enhance the nutritional value, flavor, and shelf life of Rosa roxburghii Tratt. This study demonstrated that RRFJ modulates gut microbiota and metabolites, increases short-chain fatty acid levels in the intestines, and consequently reduces pulmonary tissue injury, inflammation, and oxidative stress in murine models. Therefore, the findings from this study highlight the potential of RRFJ as a critical scientific basis for its role as a functional dietary adjunct in the management of acute lung injury.